A Semiotic Analysis of Fast-Food Restaurant Advertisements - Safitri, Hilma; Jemian, Fransiska (Universitas Pamulang, 2025)
The aim of this study was to identify and interpret both verbal and non-verbal signs within various advertisements, exploring their denotative and connotative meanings. This study employed a qualitative approach to analyze 40 fast-food advertisements from five globally recognized brands: Subway, Burger King, KFC, Pizza Hut, and McDonald's. Data collection involved identifying advertisements, reading the text, downloading images, and underlining key words, sentences, and phrases. The data were analyzed by: (1) categorizing the signs in the advertisements into two types—verbal and non-verbal; (2) analyzing the denotative and connotative meanings of these signs using theories from Barthes (1977) and Luzar & Monica (2011); and (3) drawing conclusions based on the identified denotative and connotative meanings. The selection of Barthes’ theory was aligned with the study's objective. The findings revealed a rich tapestry of signs employed to attract attention, convey messages, and persuade consumers. The results indicated the presence of 91 verbal signs, including slogans, product names, notices, and the use of capital letters, and 90 non-verbal signs, such as logos, colors, illustrations, and human imagery, within the advertisements.